2018
DOI: 10.1016/j.bpj.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Effect of Inherent Knots on Proteins Revealed by Molecular Dynamics Simulations

Abstract: A growing number of proteins have been identified as knotted in their native structures, with such entangled topological features being expected to play stabilizing roles maintaining both the global fold and the nature of proteins. However, the molecular mechanism underlying the stabilizing effect is ambiguous. Here, we combine unbiased and mechanical atomistic molecular dynamics simulations to investigate how a protein is stabilized by an inherent knot by directly comparing chemical, thermal, and mechanical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 62 publications
7
23
0
Order By: Relevance
“…Furthermore, it was also observed that kinetic stability of lattice proteins increases considerably with the complexity of knot type (98). An enhanced kinetic stability for knotted proteins was also reported in offlattice Molecular Dynamics simulations (26,134). A reduction of the intrinsic unfolding rate due to the presence of a knot in the native structure was previously reported by Yeates and co-workers through in vitro experiments that also compared an engineered knotted model system with its unknotted counterpart (84).…”
Section: Functional Advantages Of Knots In Proteinssupporting
confidence: 60%
“…Furthermore, it was also observed that kinetic stability of lattice proteins increases considerably with the complexity of knot type (98). An enhanced kinetic stability for knotted proteins was also reported in offlattice Molecular Dynamics simulations (26,134). A reduction of the intrinsic unfolding rate due to the presence of a knot in the native structure was previously reported by Yeates and co-workers through in vitro experiments that also compared an engineered knotted model system with its unknotted counterpart (84).…”
Section: Functional Advantages Of Knots In Proteinssupporting
confidence: 60%
“…29 Since the effects of this previously reported mutation at SOD1 dimer interface is not known in detail, we analyzed what effects T54R mutation has upon the monomeric and dimeric structures of SOD1 T54R . Because molecular dynamics simulation (MDS) can be an invaluable tool to study the stability of dimeric proteins, 30,31 we used this method and other computational as well as experimental techniques in this study. In the wild-type SOD1 protein, threonine-54 (T54) residue is situated in an unstructured loop (T54-loop) that connects the fourth and h beta-sheets of the eight-stranded beta barrel structure.…”
Section: Fluctuation Of the T54r Mutation-containing Loop Results In mentioning
confidence: 99%
“…Combining single-molecule fluorescence resonance energy transfer and MD simulations, the knot in TrmD was found to slide towards the C-terminal during unfolding, and the knot size kept nearly unchanged [31]. Our previous simulations showed that the knot can restrict surrounding domains to retard opening of the hydrophobic core, which was defined as a crucial step of protein unfolding [11]. Moreover, the knotted conformation was found to cooperate with dimerization to further enhance the protein stability [12].…”
Section: Introductionmentioning
confidence: 89%
“…By contrast, the dynamic information about how proteins fold into their native states is relatively less understood [7]. In particular, our past knowledge on protein folding has been challenged since identification of knotted topologies, which play essential roles in protein functioning, such as providing additional stability for maintaining the global fold and catalytic properties [8][9][10][11][12][13]. Elucidation of the folding mechanisms of knotted proteins represents an important new challenge in the protein-folding field.…”
Section: Introductionmentioning
confidence: 99%